The effect of an acute ingestion of Turkish coffee on reaction time and time trial performance. Issue 1 (December 2015) - Church, David; Hoffman, Jay; LaMonica, Michael; Riffe, Joshua; Hoffman, Mattan; Baker, Kayla; Varanoske, Alyssa; Wells, Adam; Fukuda, David; Stout, Jeffrey
Abstract Background The purpose of this study was to examine the ergogenic benefits of Turkish coffee consumed an hour before exercise. In addition, metabolic, cardiovascular, and subjective measures of energy, focus and alertness were examined in healthy, recreationally active adults who were regular caffeine consumers (>200 mg per day). Methods Twenty males (n = 10) and females (n = 10), age 24.1 ± 2.9 y; height 1.70 ± 0.09 m; body mass 73.0 ± 13.0 kg (mean ± SD), ingested both Turkish coffee [3 mg · kg−1 BW of caffeine, (TC)], and decaffeinated Turkish coffee (DC) in a double-blind, randomized, cross-over design. Performance measures included a 5 km time trial, upper and lower body reaction to visual stimuli, and multiple object tracking. Plasma caffeine concentrations, blood pressure (BP), heart rate and subjective measures of energy, focus and alertness were assessed at baseline (BL), 30-min following coffee ingestion (30+), prior to endurance exercise (PRE) and immediately-post 5 km (IP). Metabolic measures [VO2, VE, and respiratory exchange rate (RER)] were measured during the 5 km. Results Plasma caffeine concentrations were significantly greater during TC (p < 0.001) at 30+, PRE, and IP compared to DC. Significantly higher energy levels were reported at 30+ and PRE for TC compared to DC. Upper body reaction performance (p = 0.023) and RER (p = 0.019) were significantly higher for TC (85.1 ± 11.6 "hits, " and 0.98 ± 0.05 respectively) compared to DC (81.2 ± 13.7 "hits, " and 0.96 ± 0.05, respectively). Although no significant differences (p = 0.192) were observed in 5 km run time, 12 of the 20 subjects ran faster (p = 0.012) during TC (1662 ± 252 s) compared to DC (1743 ± 296 s). Systolic BP was significantly elevated during TC in comparison to DC. No other differences (p > 0.05) were noted in any of the other performance or metabolic measures. Conclusions Acute ingestion of TC resulted in a significant elevation in plasma caffeine concentrations within 30-min of consumption. TC ingestion resulted in significant performance benefits in reaction time and an increase in subjective feelings of energy in habitual caffeine users. No significant differences were noted in time for the 5 km between trials, however 60 % of the participants performed the 5 km faster during the TC trial and were deemed responders. When comparing TC to DC in responders only, significantly faster times were noted when consuming TC compared to DC. No significant benefits were noted in measures of cognitive function.